2020
DOI: 10.1128/msystems.00821-20
|View full text |Cite
|
Sign up to set email alerts
|

Struggle To Survive: the Choir of Target Alteration, Hydrolyzing Enzyme, and Plasmid Expression as a Novel Aztreonam-Avibactam Resistance Mechanism

Abstract: Aztreonam-avibactam is a promising antimicrobial combination against multidrug-resistant organisms, such as carbapenemase-producing Enterobacterales. Resistance to aztreonam-avibactam has been found, but the resistance mechanism remains poorly studied. We recovered three Escherichia coli isolates of an almost identical genome but exhibiting varied aztreonam-avibactam resistance. The isolates carried a cephalosporinase gene, blaCMY-42, on IncIγ plasmids with a single-nucleotide variation in an antisense RNA-enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…68,69 MBL-producing Enterobacterales that coharbor an AmpC, such as bla CMY , may be particularly prone to developing ATM-AVI resistance as mutations in the gene encoding for this enzyme have also been shown to cause ATM-AVI resistance. 70,71 The insertion is not associated with MBL β-lactamases and appears limited to E. coli isolates.…”
mentioning
confidence: 99%
“…68,69 MBL-producing Enterobacterales that coharbor an AmpC, such as bla CMY , may be particularly prone to developing ATM-AVI resistance as mutations in the gene encoding for this enzyme have also been shown to cause ATM-AVI resistance. 70,71 The insertion is not associated with MBL β-lactamases and appears limited to E. coli isolates.…”
mentioning
confidence: 99%
“…Similar 4-aa insertions have been reported among NDM-5–producing E. coli as a cause of elevated MICs of ATM, related to impeding accessibility to the binding site of PBP-3, and therefore were involved in ATM/AVI resistance in addition to CMY production ( 28 ). Ma et al reported that the insertion alone has a minor effect on ATM/AVI resistance levels ( 29 ), but resistance could be achieved when combined with CMY production ( 29 ). Other studies reported that CMY variants with a glycine residue at position 231 exhibited enhanced hydrolysis against ATM ( 30 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…The high level of association of carbapenemases to the NDM-5 and RMTase genes will limit the choice of therapeutics available for treating infections because of those multidrug-resistant bacteria. Several isolates were identified that were resistant to the β-lactam/inhibitor combination ATM/AVI, a potential future treatment for infections caused by NDM-producing bacteria ( 28 , 29 ). The transmission of successful plasmids, both within and between species, was identified as a major factor in the increasing prevalence of NDM-producing Enterobacterales .…”
Section: Discussionmentioning
confidence: 99%
“…For the other remaining isolates, co-production and/or hyperexpression of ESBL and AmpC-type determinants could have contributed to the high MIC values of ATM in combination with AVI. Notably, the association of CMY-42 and the YRIK insertion in PBP3 has been demonstrated to confer resistance to ATM-AVI in E. coli by mutagenesis experiments [ 77 ]. ATM-AVI showed low antimicrobial activity against 15% of S. maltophilia isolates, even if potential resistance mechanisms were not investigated.…”
Section: Discussionmentioning
confidence: 99%